Apertura y bidimensionalidad. El sentido ontológico de la verdad en Ser y tiempo - Domergue, Tomás (2022)
As it is well known, throughout Being and Time Heidegger distinguishes between an ontic (Entdecken) and an ontological (Erschlossenheit) sense of truth. Whereas the first one involves truth, insofar as a way in which the Dasein can be concerning beings, the second one corresponds to the manner in which the Dasein opens and comprehends their being. In this paper, we will focus on developing the phenomenological aspect of the second sense of truth and its relation with the first one. We will recreate, first and foremost, Heidegger’s characterization of the ontological sense. Then, we will make use of the asymmetry between both kinds of senses to inquire about the problem of normativity presupposed in his work.